INTEGRATING YOUTUBE APPLICATION FOR REMOTE LEARNING: THE VIRTUES AND CHALLENGES - Eka Wulandari; Arina Chusnatayaini (The Journal Of English Teaching For Young And Adult Learners, 2022)
Youtube application is a widely used social media platform that has reached its peak popularity nowadays.All people, young and old, are familiar to this. In this pandemic era, the use of this platform can beconsidered as one of the best alternatives for teaching English online due to its familiarity, effectiveness,and attractive features. It also offers various information needed not only for the teachers but for thestudents as well and it can be utilized as a two-way communication for teaching and learning process too.This application also provides authentic learning materials for the learners. Based on this consideration,this paper will review some of the virtues and challenges we can find by employing Youtube applicationfor our emergency remote learning during this Covid 19 outbreak. It is expected that this discussion willbe able to give alternatives for improving our teaching and learning process quality during this difficulttime.